Effect of atenolol and enalapril treatment on oxidative stress parameters in patients with essential hypertension - Deoghare, Shashank; Kantharia, N. D. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Oxidative stress has emerged as an importantfactor in the pathophysiologyof hypertension. It alsocontributes to variouscomplicationsassociated with hypertension like vascular injury, atherosclerosis, renal dysfunction, and hypertensive end-organ damage. Present study was done to evaluate the effect of atenololand enalapril, twocommonly prescribed antihypertensive drugs, on oxidative stress in patients with hypertension. Method: Sixty newly diagnosed hypertensive patients wererandomlyassigned to either atenolol (n = 30) or enalapriltherapy(n = 30) and followed up forthe period ofthree months. Twenty normotensive healthy volunteers served as control.Plasma malondialdehyde, superoxide dismutase and catalaselevelswere measuredat the time of enrollment and at the end of three months of antihypertensive treatment. Results: Plasmamalondialdehyde was significantly increased whereas superoxide dismutase and catalase were significantly reduced in newly diagnosed hypertensive patients compared to controls. After three months of enalapril therapy, plasmamalondialdehydewassignificantly reduced and superoxide dismutase and catalase were significantlyelevated. Atenolol therapyhad no effect on theseoxidative stress parameters. Conclusions: Enalapril therapy significantly reduced oxidative stress in contrast toatenolol.Thus enalapriltherapymay prove beneficial compared to atenolol bypreventing oxidative stressand related complications inhypertension in view of life long therapy required for the treatment of hypertension.